USING THE SOCRATES METHOD IN IMPROVING THE QUALITY OF EDUCATION IN PEDAGOGICAL UNIVERSITIES - Akhmedov B.A.; Makhmudova D.M.; Akhmedjonov D.G. (Sciental Journals Publishing, 2024)
It is shown that Socrates' method, his dialogue, is a kind of laboratory, an animated search field, assuming the presence of two interlocutors. There is no real wisdom outside of Socrates' dialogue, but only a lot of knowledge. The emergence of information computer systems makes it possible to expand the cognitive possibilities of dialogue. Such a virtual dialogue does not diminish the importance of a live, direct dialogue, but complements it by changing the form of the traditional educational process.
Keywords: Dialogue; Truth; Knowledge; Self-knowledge; Virtual dialogue